2006
DOI: 10.1093/brain/awl344
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe lesions and semantic impairment: a comparison of herpes simplex virus encephalitis and semantic dementia

Abstract: Both herpes simplex virus encephalitis (HSVE) and semantic dementia (SD) typically affect anterior temporal lobe structures. Using voxel-based morphometry (VBM), this study compared the structural damage in four HSVE patients having a semantic deficit particularly affecting knowledge of living things and six SD patients with semantic impairment across all categories tested. Each patient was assessed relative to a group of control subjects. In both patient groups, left anterior temporal damage extended into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
122
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 88 publications
13
122
0
1
Order By: Relevance
“…However, our results revealed longer involvement of the activation of the anterior part of inferior temporal lobe for semantic compared with phonological task. This result confirms the crucial role of this region for the semantic access (Mummery et al, 2000;Marinkovic et al, 2003;Bright et al, 2004;Gorno-Tempini et al, 2004;Noppeney et al, 2007;Fujimaki et al, 2009;Lambon Ralph et al, 2009;Binney et al, 2010;Visser et al, 2010). This region could serve as a hub within the widespread semantic system.…”
Section: Spatiotemporal Integration Of Phonological and Semantic Procsupporting
confidence: 80%
“…However, our results revealed longer involvement of the activation of the anterior part of inferior temporal lobe for semantic compared with phonological task. This result confirms the crucial role of this region for the semantic access (Mummery et al, 2000;Marinkovic et al, 2003;Bright et al, 2004;Gorno-Tempini et al, 2004;Noppeney et al, 2007;Fujimaki et al, 2009;Lambon Ralph et al, 2009;Binney et al, 2010;Visser et al, 2010). This region could serve as a hub within the widespread semantic system.…”
Section: Spatiotemporal Integration Of Phonological and Semantic Procsupporting
confidence: 80%
“…Brambati et al 2006;Noppeney, Patterson, Tyler, Moss, Stamatakis, Bright, Mummery, & Price, 2007;Papagno, Capasso, & Miceli, 2009). This result motivates the use of fMRI longitudinally in patients to study the deterioration of object knowledge with the progression of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Third, results from the outcome of epilepsy-related resections are complicated by two factors: (i) longstanding epilepsy might lead to changes in neural organization, and, indeed, recent imaging studies have shown that white matter connectivity and neurotransmitter function are significantly altered in this condition (27,28); and (ii) this procedure is unilateral, whereas SD patients have bilateral temporal lobe atrophy. Other neurological disorders, such as herpes simplex virus encephalitis, do produce semantic impairment when damage affects the same bilateral temporal lobe regions as semantic dementia (9,29).…”
mentioning
confidence: 99%